Case studies of existing human tissue repositories : "best practices" for a biospecimen resource for the genomic and proteomic era - Eiseman, Elisa (Online Rand research documents., 2003)
Case studies of twelve existing human biospecimen repositories performed to evaluate their utility for genomics- and proteomics-based cancer research and to identify?best practices? in collection, processing, annotation, storage, privacy, ethical concerns, informed consent, business plans, operations, intellectual property rights, public relations, marketing, and education that would be useful in designing a national biospecimen network.